Epidemiological aspects of enteroparasitosis at daycare centers in the city of Botucatu, State of São Paulo, Brazil - Mascarini, Luciene Maura [UNESP]; Donalisio, Maria Rita [UNESP] (Associação Brasileira de Pós -Graduação em Saúde Coletiva, 2006)
Estimou-se a prevalência e a incidência de parasitas intestinais em crianças e funcionários de 5 creches municipais em Botucatu/SP. Foram realizados dois estudos seccionais em 2002 (N=379) e 2003 (N=397) e um estudo longitudinal observacional, onde as crianças de 2002 e 2003 foram seguidas por um ano. Foram aplicados questionários nos funcionários e nos pais das crianças, onde foram coletadas as seguintes variáveis: nível sócio-econômico, hábitos sanitários, moradia, idade, sexo e presença de animais domésticos. Foram realizados exames coproparasitológicos nas crianças das creches. A prevalência de enteroparasitas em 2002 foi de 76,74% e 34% em 2003. As variáveis associadas à presença de enteroparasitas no ano de 2002 foram: localização das creches (OR=0,27 IC=0,15-0,47), renda familiar (OR=4,38 IC=1,91-10,04), sexo (OR=0,52 IC=0,32-0,85), faixa etária (OR=2,08 IC=1,06-4,08) e presença de animais domésticos na casa (OR=1,85 IC=1,10-3,11); em 2003, as variáveis foram: creche localizada em bairro periférico (OR=0,49 IC=0,31-0,78), renda familiar (OR=3,69 IC=2,19-6,24), nível educacional da mãe (OR=6,19 IC=1,81-21,21), sexo (OR=0,36 IC=0,36-0,93) e presença de animais domésticos (OR=1,68 IC=1,01-2,79). A coorte foi integrada por 253 crianças apresentando incidência de 23,22%. Os dados deste estudo evidenciam situações de risco em populações específicas (creches) e poderiam ser utilizados por Instituições que promovem o cuidado com as crianças.

OBJECTIVE: To estimate the prevalence and incidence of intestinal parasites in children and staff members of 5 municipal daycare centers in Botucatu/SP. Two cross-sectional studies were carried out in 2002 (N=379) and 2003 (N=397) and a longitudinal observational experiment in which the children from 2002 and 2003 were evaluated for a year. Questionnaires were given to staff members and parents of the children, where the following variables were recorded: socioeconomic status, sanitary habits, home, age, gender and presence of domestic animals. Coproparasitologic tests were carried out in child daycare centers. The enteroparasite prevalence was 76.74% in 2002 and 34% in 2003. The variables associated with presence of enteroparasites in the investigation carried out in 2002 were: location of daycare centers (OR=0.27 CI=0.15-0.47); family salary (OR=4.38 CI=1.91-10.04); gender (OR=0.52 CI=0.32-0.85); child's age group (OR=2.08 CI=1.06-4.08), and presence of pets at home (OR=1.85 CI=1.10-3.11); in 2003, the variables were: daycare centers located in peripheral region (OR=0.49 CI=0.31-0.78), family salary (OR=3.69 CI=2.19-6.24); mother's education (OR=6.19 CI=1.81-21.21); gender (OR=0.58 CI=0.36-0.93), and presence of pets (OR=1.68 CI=1.01-2.79). The cohort had 253 children with an incidence of 23.22%. Data from this study highlighted situations of risk in specific populations (daycare centers), which could be useful for other childcare institutions.
Aspectos epidemiológicos das enteroparasitoses em creches na cidade de Botucatu, Estado de São Paulo, Brasil
Keywords: Crianças; Parasitas intestinais; Creches; Epidemiologia; Child; Intestinal parasites; Daycare center; Epidemiology